Class I HDAC Inhibitor Improves Synaptic Proteins and Repairs Cytoskeleton Through Regulating Synapse-Related Genes In vitro and In vivo - Han, Ying; Chen, Le; Guo, Yu; Wang, Chunyang; Zhang, Chenghong; Kong, Li; Ma, Haiying (Frontiers in Aging Neuroscience, 2021)
β-amyloid (Aβ) is an important protein molecule in the pathology of Alzheimer's Disease (AD). Accumulation of Aβ leads to the loss of dendritic spines and synapses. These impairments can be ameliorated by histone deacetylase inhibitors (HDACIs). However, the mechanisms of HDACIs underlying the effect on synapse are not fully understood. In this study, we examined the relationship between HDAC activity and synapse-related gene and protein by the administration of a class I HDAC inhibitor, BG45, in the exogenous Aβ-treated cells and mice. Our studies showed that the treatment of HF-488-Aβ1-42 to SH-SY5Y cells first increased the expression of postsynaptic dendritic protein (PSD), then decreased it after 36 h. BG45 can reduce Aβ aggregation induced by HF-488-Aβ1-42 in SH-SY5Y cells, and it can increase the expression of PSD-95 as well as spinophilin and cytoskeletal protein. Similar to the results in vitro, PSD-95 in the hippocampus was temporarily increased in the early days of intravenous injection HF-488-Aβ1-40 to the mice, followed by the decreased expression of PSD-95 at the 9th day. In further studies, for the mice treated with Aβ for 9 days, we found that BG decreased the expression of HDAC1 and 2, increased the expression of PSD-95, spinophilin and SYP. Our data also showed that BG45 upregulated levels of three synapse-related genes and proteins GRIK2, SCN3B, SYNPR. These findings suggest that the exogenous Aβ may stimulate transiently the expression of PSD-95 at an early stage, but subsequently contribute to synaptic defects. HDAC1 and 2 are involved in synaptic defects, and BG45 may improve the expression of synaptic and cytoskeletal protein and repair cytoskeletal damage by specifically inhibiting HDAC1 and 2, thereby modulating synapse-related gene. BG45 might be a potential therapeutic agent for the treatment of an early stage of Aβ-related neurodegenerative disease.